Preliminary Optimization of the Complicated Interplanetary Flight Path of the Spacecraft with Electric Propulsion. (2017) - Konstantinov, Mikhail; Thein, Min
Abstract: The complicated interplanetary flight path of spacecraft with electric propulsion using multiple gravitational maneuvers is examined. The method developed is based on the use of solutions of the auxiliary problem for SC with chemical propulsion systems. The results of the solution of this auxiliary problem allowed rational flight paths of spacecraft with electric propulsion to be identified and the the flight paths optimized. The auxiliary problem of the analyzed particular flight path is formulated as a problem of mathematical programming. A large number of equality and inequality constraints must be satisfied in solving this problem. The complicated flight path of the spacecraft to Jupiter is discussed as a typical example. The Earth, Venus and Mars are considered as the intermediate planets where the gravitational maneuvers will be accomplished.